Finding Dorothy: a novel (Ballantine Books, Random House Large Print, 2019)
"This richly imagined novel tells the story behind The Wonderful Wizard of Oz, the book that inspired the iconic film, through the eyes of author L. Frank Baum's intrepid wife, Maud. Hollywood, 1938: As soon as she learns that M-G-M is adapting her late husband's masterpiece for the screen, seventy-seven-year-old Maud Gage Baum sets about trying to finagle her way onto the set. Nineteen years after Frank's passing, Maud is the only person who can help the producers stay true to the spirit of the book--because she's the only one left who knows its secrets. But the moment she hears Judy Garland rehearsing the first notes of "Over the Rainbow," Maud recognizes the yearning that defined her own life story: from her youth as a suffragette's daughter to her coming of age as one of the first women in the Ivy League, from her blossoming romance with Frank to the hardscrabble prairie years that inspired The Wonderful Wizard of Oz. Judy reminds Maud of a young girl she cared for and tried to help in South Dakota, a dreamer who never got her happy ending. Now, with the young actress under pressure from the studio as well as her ambitious stage mother, Maud resolves to protect her--the way she tried so hard to protect the real Dorothy"--

A piece of the world: a novel (William Morrow, an imprint of HarperCollinsPublishers, 2017)
To Christina Olson, the entire world was her familys remote farm in the small coastal town of Cushing, Maine. Born in the home her family had lived in for generations, and increasingly incapacitated by illness, Christina seemed destined for a small life. Instead, for more than twenty years, she was host and inspiration for the artist Andrew Wyeth, and became the subject of one of the best known American paintings of the twentieth century.

The personal librarian (Berkley, 2021)
"The remarkable, little-known story of Belle da Costa Greene, J. P. Morgan's personal librarian-who became one of the most powerful women in New York despite the dangerous secret she kept in order to make her dreams come true, from New York Times bestselling author Marie Benedict and acclaimed author Victoria Christopher Murray. In her twenties, Belle da Costa Greene is hired by J. Pierpont Morgan to curate a collection of rare manuscripts, books, and artwork for his newly built Morgan Library. Belle becomes a fixture on the New York society scene and one of the most powerful people in the art and book world, known for her impeccable taste and shrewd negotiating for critical works as she helps build a world-class collection. But Belle has a secret, one she must protect at all costs. She was born not Belle da Costa Greene but Belle Marion Greener. She is the daughter of Richard Greener, the first Black graduate of Harvard and well-known advocate for equality. Belle's complexion isn't dark because of her alleged Portuguese heritage that lets her pass as white-her complexion is dark because she is African American. The Personal Librarian tells the story of an extraordinary woman, famous for her intellect, style, and wit, and shares the lengths she must go-for the protection of her family and her legacy-to preserve her carefully crafted white identity in the racist world in which she lives"--

The dictionary of lost words: a novel (Reese's book club, ,, 2022)
"The Dictionary of Lost Words is a work of fiction. All incidents and dialogue, and all characters with the exception of some well-known historical figures, are products of the author's imagination and are not to be construed as real. Before the lost word, there was another. It arrived at the Scriptorium in a second-hand envelope, the old address crossed out and Dr Murray, Sunnyside, Oxford, written in its place. It was Da's job to open the post and mine to sit on his lap, like a queen on her throne, and help him ease each word out of its folded cradle. He'd tell me what pile to put it on and sometimes he'd pause, cover my hand with his, and guide my finger up and down and around the letters, sounding them into my ear. He'd say the word, and I would echo it, then he'd tell me what it meant"--

Lady Clementine (Sourcebooks Landmark, 2020)
A historical tale inspired by the life of Clementine Churchill that traces her unflinching role in protecting the life and wartime agendas of her husband, Winston Churchill.

Sister stardust: a novel (Hanover Square Press, Thorndike Pr, 2022)
In her first novel inspired by a true story, Jane Green re-imagines the life of troubled icon Talitha Getty in this transporting story from a forgotten chapter of the Swinging '60s. From afar Talitha's life seemed perfect. In her twenties, and already a famous model and actress, she moved from London to a palace in Marrakesh, with her husband Paul Getty, the famous oil heir. There she presided over a swirling ex-pat scene filled with music, art, free love and a counterculture taking root across the world. When Claire arrives in London from her small town, she never expects to cross paths with a woman as magnetic as Talitha Getty. Yearning for the adventure and independence, she's swept off to Marrakesh, where the two become kindred spirits. But beneath Talitha's glamourous facade lurks a darkness few can understand. As their friendship blossoms and the two grow closer, the realities of Talitha's precarious existence set off a chain of dangerous events that could alter Claire's life forever.

The widows (Minotaur Books, 2019)
Vowing revenge against her sheriff husband's killers in 1924 Ohio, Lily Ross offers help to a fellow widow and uncovers dangerous evidence revealing her husband's corrupt secret life and the complexities that triggered his death.

The only woman in the room (Sourcebooks Inc, Sourcebooks, Sourcebooks Landmark, 2019)
A beautiful woman escapes her Austrian arms-dealer husband to become Hollywood legend Hedy Lamarr while hiding a secret double life as a Jewish scientist and sharing vital information about the Third Reich.

Her hidden genius: a novel (Sourcebooks Landmark, 2022)
"Rosalind Franklin knows if she just takes one more X-ray picture-one more after thousands-she can unlock the building blocks of life. Never again will she have to listen to her colleagues complain about her, especially Maurice Wilkins who'd rather conspire about genetics with James Watson and Francis Crick than work alongside her. Then it finally happens-the double helix structure of DNA reveals itself to her with perfect clarity. But what happens next, Rosalind could have never predicted. Marie Benedict's next powerful novel shines a light on a woman who died to discover our very DNA, a woman whose contributions were suppressed by the men around her but whose relentless drive advanced our understanding of humankind"--

Fates and traitors: a novel of John Wilkes Booth (Dutton, 2016)
A reimagining of the life of Lincoln's assassin describes Booth's tumultuous childhood on a Maryland farm and rise to the ballrooms of Washington, D.C., at the sides of four women before he became obsessed with avenging the Confederacy.

Carnegie's maid (Sourcebooks Landmark, Books on Tape, 2018)
Clara Kelley is not who they think she is. She's not the experienced Irish maid who was hired to work in one of Pittsburgh's grandest households. She's a poor farmer's daughter with nowhere to go and nothing in her pockets. But the other woman with the same name has vanished, and pretending to be her just might get Clara some money to send back home. If she can keep up the ruse, that is. Serving as a lady's maid in the household of Andrew Carnegie requires skills he doesn't have, answering to an icy mistress who rules her sons and her domain with an iron fist. What Clara does have is a resolve as strong as the steel Pittsburgh is becoming famous for, coupled with an uncanny understanding of business, and Andrew begins to rely on her. But Clara can't let her guard down, not even when Andrew becomes something more than an employer. Revealing her past might ruin her future -- and her family's.

The Diamond Eye (Harper Large Print, an imprint of HarperCollinsPublishers, William Morrow, an imprint of HarperCollins Publishers, William Morrow, an imprint of HarperCollinsPublishers, 2022)
"The New York Times bestselling author of The Rose Code returns with an unforgettable World War II tale of a quiet bookworm who becomes history's deadliest female sniper. Based on a true story. In 1937 in the snowbound city of Kiev (now known as Kyiv), wry and bookish history student Mila Pavlichenko organizes her life around her library job and her young son--but Hitler's invasion of Ukraine and Russia sends her on a different path. Given a rifle and sent to join the fight, Mila must forge herself from studious girl to deadly sniper--a lethal hunter of Nazis known as Lady Death. When news of her three hundredth kill makes her a national heroine, Mila finds herself torn from the bloody battlefields of the eastern front and sent to America on a goodwill tour. Still reeling from war wounds and devastated by loss, Mila finds herself isolated and lonely in the glittering world of Washington, DC--until an unexpected friendship with First Lady Eleanor Roosevelt and an even more unexpected connection with a silent fellow sniper offer the possibility of happiness. But when an old enemy from Mila's past joins forces with a deadly new foe lurking in the shadows, Lady Death finds herself battling her own demons and enemy bullets in the deadliest duel of her life. Based on a true story, The Diamond Eye is a haunting novel of heroism born of desperation, of a mother who became a soldier, of a woman who found her place in the world and changed the course of history forever."--

The Mitford affair (Thorndike Press large print core, ,, 2023)
"Between the World Wars, the six Mitford sisters--each more beautiful, brilliant, and eccentric than the next--dominate the English scenes. Though they've weathered scandals before, the family falls into disarray when Diana divorces her wealthy husband to marry a fascist leader and Unity follows her sister's lead all the way to Munich, inciting rumors that she's become Hitler's mistress. As the Nazis rise in power, novelist Nancy Mitford grows suspicious of her sisters' constant visits to Germany and the high-ranking fascist company they keep. When she overhears alarming conversations and uncovers disquieting documents, Nancy must make excruciating choices as Great Britain goes to war with Germany. Probing the torrid political climate in the lead-up to WWII and the ways that seemingly sensible people can be sucked into radical action, The Mitford Affair follows Nancy's valiant efforts to stop the Nazis from taking over Great Britain, choosing between loyalty to her country and allegiance to her family, and forcing her to learn exactly how personal is the political"--

Love and ruin: a novel (Ballantine Books, Findaway World, LLC, 2018)
"The bestselling author of The Paris Wife returns to the subject of Ernest Hemingway in a novel about his passionate, stormy marriage to Martha Gellhorn--a fiercely independent, ambitious young woman who would become one of the greatest war correspondents of the twentieth century In 1937, twenty-eight-year-old Martha Gellhorn travels alone to Madrid to report on the atrocities of the Spanish Civil War and becomes drawn to the stories of ordinary people caught in the devastating conflict. It's the adventure she's been looking for and her chance to prove herself a worthy journalist in a field dominated by men. But she also finds herself unexpectedly--and uncontrollably--falling in love with Hemingway, a man on his way to becoming a legend. In the shadow of the impending Second World War, and set against the turbulent backdrops of Madrid and Cuba, Martha and Ernest's relationship and their professional careers ignite. But when Ernest publishes the biggest literary success of his career, For Whom the Bell Tolls, they are no longer equals, and Martha must make a choice: surrender to the confining demands of being a famous man's wife or risk losing Ernest by forging a path as her own woman and writer. It is a dilemma that could force her to break his heart, and hers. Heralded by Ann Patchett as "the new star of historical fiction," Paula McLain brings Gellhorn's story richly to life and captures her as a heroine for the ages: a woman who will risk absolutely everything to find her own voice"--

Booth: a novel (G. P. Putnam's Sons, G.P. Putnam's Sons, 2022)
In 1822, a secret family moves into a secret cabin some thirty miles northeast of Baltimore, to farm, to hide, and to bear ten children over the course of the next sixteen years. Junius Booth—breadwinner, celebrated Shakespearean actor, and master of the house in more ways than one—is at once a mesmerizing talent and a man of terrifying instability. One by one the children arrive, as year by year, the country draws frighteningly closer to the boiling point of secession and civil war. As the tenor of the world shifts, the Booths emerge from their hidden lives to cement their place as one of the country’s leading theatrical families. But behind the curtains of the many stages they have graced, multiple scandals, family triumphs, and criminal disasters begin to take their toll, and the solemn siblings of John Wilkes Booth are left to reckon with the truth behind the destructively specious promise of an early prophecy. Booth is a startling portrait of a country in the throes of change and a vivid exploration of the ties that make, and break, a family.

Beneath a scarlet sky (Lake Union Publishing, 2018)
"Pino Lella wants nothing to do with the war or the Nazis. Hes a normal Italian teenagerobsessed with music, food, and girlsbut his days of innocence are numbered. When his family home in Milan is destroyed by Allied bombs, Pino joins an underground railroad helping Jews escape over the Alps, and falls for Anna, a beautiful widow six years his senior.In an attempt to protect him, Pinos parents force him to enlist as a German soldiera move they think will keep him out of combat. But after Pino is injured, he is recruited at the tender age of eighteen to become the personal driver for Adolf Hitlers left hand in Italy, General Hans Leyers, one of the Third Reichs most mysterious and powerful commanders.Now, with the opportunity to spy for the Allies inside the German High Command, Pino endures the horrors of the war and the Nazi occupation by fighting in secret, his courage bolstered by his love for Anna and for the life he dreams they will one day share." - Amazon.

THE BOOK of LONGINGS : : A NOVEL / (Viking, 2020)
"In her fourth work of fiction, Sue Monk Kidd brings her acclaimed narrative gifts to imagine the story of a young woman named Ana. Raised in a wealthy family in Sepphoris with ties to the ruler of Galilee, she is rebellious and ambitious, a relentless seeker with a brilliant, curious mind and a daring spirit. She yearns for a pursuit worthy of her life, but finds no outlet for her considerable talents. Defying the expectations placed on women, she engages in furtive scholarly pursuits and writes secret narratives about neglected and silenced women. When she meets the eighteen-year-old Jesus, each is drawn to and enriched by the other's spiritual and philosophical ideas. He becomes a floodgate for her intellect, but also the awakener of her heart. Their marriage unfolds with love and conflict, humor and pathos in Nazareth, where Ana makes a home with Jesus, his brothers, James and Simon, and their mother, Mary. Here, Ana's pent-up longings intensify amid the turbulent resistance to the Roman occupation of Israel, partially led by her charismatic adopted brother, Judas. She is sustained by her indomitable aunt Yaltha, who is searching for her long-lost daughter, as well as by other women, including her friend Tabitha, who is sold into slavery after she was raped, and Phasaelis, the shrewd wife of Herod Antipas. Ana's impetuous streak occasionally invites danger. When one such foray forces her to flee Nazareth for her safety shortly before Jesus's public ministry begins, she makes her way with Yaltha to Alexandria, where she eventually finds refuge and purpose in unexpected surroundings. Grounded in meticulous historical research and written with a reverential approach to Jesus's life that focuses on his humanity, The Book of Longings is an inspiring account of one woman's bold struggle to realize the passion and potential inside her, while living in a time, place, and culture devised to silence her"--

Caroline: Little House, revisited (Little house, ,, 2017)
"In the frigid days of February, 1870, Caroline Ingalls, her husband Charles, and their little girls, Mary and Laura, leave the familiar comforts of the Big Woods of Wisconsin and head west to settle in a beautiful, unpredictable land full of promise and peril--the Kansas Indian Territory. The pioneer life is a hard one, especially for a pregnant woman with no friends or kin to turn to for comfort or help. The burden of work must be shouldered alone, sickness tended without the aid of doctors, and babies birthed without the accustomed hands of mothers or sisters. But Caroline's world is also full of tender joys. In adapting to this strange new place and transforming a rough log house built by Charles into a home, Caroline must draw on untapped wells of strength she does not know she possesses. For more than eighty years, generations of readers have been enchanted by the adventures of the American frontier's most famous child, Laura Ingalls Wilder, in the Little House books. Now, that familiar story is retold in this captivating tale of family, fidelity, hardship, love, and survival that vividly reimagines our past."--

The mystery of Mrs. Christie: a novel (Audible Studios on BrillianceAudio, ,, 2021)
"December 1926: England unleashes the largest manhunt in its history. The object of the search is not an escaped convict or a war criminal, but the missing wife of a WWI hero, up-and-coming mystery author Agatha Christie. When her car is found wrecked, empty, and abandoned near a natural spring, the country is in a frenzy. Eleven days later, Agatha reappears, claiming amnesia. She provides no answers for her disappearance. That is...until she writes a very strange book about a missing woman, a murderous husband, and a plan to expose the truth. What role did her unfaithful husband play? And what was he not telling investigators? THE MYSTERY OF MRS. CHRISTIE explores one strong woman's successful endeavor to take her history into her own hands"--

The diamond eye: a novel (HarperAudio, William Morrow, an imprint of HarperCollinsPublishers, 2022)
"The New York Times bestselling author of The Rose Code returns with an unforgettable World War II tale of a quiet bookworm who becomes history's deadliest female sniper. Based on a true story. In 1937 in the snowbound city of Kiev (now known as Kyiv), wry and bookish history student Mila Pavlichenko organizes her life around her library job and her young son--but Hitler's invasion of Ukraine and Russia sends her on a different path. Given a rifle and sent to join the fight, Mila must forge herself from studious girl to deadly sniper--a lethal hunter of Nazis known as Lady Death. When news of her three hundredth kill makes her a national heroine, Mila finds herself torn from the bloody battlefields of the eastern front and sent to America on a goodwill tour. Still reeling from war wounds and devastated by loss, Mila finds herself isolated and lonely in the glittering world of Washington, DC--until an unexpected friendship with First Lady Eleanor Roosevelt and an even more unexpected connection with a silent fellow sniper offer the possibility of happiness. But when an old enemy from Mila's past joins forces with a deadly new foe lurking in the shadows, Lady Death finds herself battling her own demons and enemy bullets in the deadliest duel of her life. Based on a true story, The Diamond Eye is a haunting novel of heroism born of desperation, of a mother who became a soldier, of a woman who found her place in the world and changed the course of history forever."--